2016
DOI: 10.1371/journal.pone.0148675
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure of Macrobiota and Environmental Parameters in Shallow Water Hydrothermal Vents off Kueishan Island, Taiwan

Abstract: Hydrothermal vents represent a unique habitat in the marine ecosystem characterized with high water temperature and toxic acidic chemistry. Vents are distributed at depths ranging from a few meters to several thousand meters. The biological communities of shallow-water vents have, however, been insufficiently studied in most biogeographic areas. We attempted to characterize the macrofauna and macroflora community inhabiting the shallow-water vents off Kueishan Island, Taiwan, to identify the main abiotic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(85 citation statements)
references
References 34 publications
2
83
0
Order By: Relevance
“…Shallow marine hydrothermal vent systems are frequently characterized by biota, such as nematodes and polychaetes, devoid of easily fossilizable parts, able to live in extreme ecological conditions where macrofauna is not present (Kamenev et al, 1993;Hoaki et al, 1995). As a general rule in the vicinity of the vent outlets the diversity decreases, the dominance of tolerant spe-cies increases (Melwani and Kim, 2008;Zeppilli and Danovaro, 2009;Karlen et al, 2010;Chan et al, 2016) and the bottom waters are frequently corrosive to calcium carbonate inhibiting the calcification of shelled organisms (Cigliano et al, 2010;Ricevuto et al, 2012;Boatta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Shallow marine hydrothermal vent systems are frequently characterized by biota, such as nematodes and polychaetes, devoid of easily fossilizable parts, able to live in extreme ecological conditions where macrofauna is not present (Kamenev et al, 1993;Hoaki et al, 1995). As a general rule in the vicinity of the vent outlets the diversity decreases, the dominance of tolerant spe-cies increases (Melwani and Kim, 2008;Zeppilli and Danovaro, 2009;Karlen et al, 2010;Chan et al, 2016) and the bottom waters are frequently corrosive to calcium carbonate inhibiting the calcification of shelled organisms (Cigliano et al, 2010;Ricevuto et al, 2012;Boatta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At upper bathyal depths, inputs from photosynthetic organisms increase and dependence on chemosynthetic carbon would proportionally decrease (Levin & Michener 2002, Levin 2005, Levin & Mendoza 2007. In shallow vents the major food source is usually photosynthetic rather that chemosynthetic (Kharlamenko et al 1995, Tarasov et al 2005, Chan et al 2016. However, despite this lower relative abundance of sulfur bacteria, they can still be used as food source in some shallow vent locations (Thiermann et al 1997, Bosley et al 2002, Forrest 2004, Comeault et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that hydrothermal vents are the most important habitat factor for the vent crab X. testudinatus. This crab could not be found otherwise along the shallow coast of Kueishan Island outside the hydrothermal vent area [18]. The main reason might be the acidity and sulfide toxicity of hydrothermal vent waters that made it impossible for the predators of X. testudinatus living in hydrothermal vent field for extended times.…”
Section: Crab Distribution In the Hydrothermal Vent Areamentioning
confidence: 95%
“…The M. distinguendus may slowly evolve detoxification mechanisms against toxic hydrothermal vent waters that expand its habitat into this area. On the other hand, Xenograpsus testudinatus highly rely on toxic hydrothermal vent waters [18], Fig 7. A survey of the distribution of female and male morphological measurements for the all crabs, wet body weight (a), carapace width (b), and chela length (c).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation